Transport properties of ionized species - Selle, Stefan; Riedel, Uwe (Annals of the New York Academy of Sciences, 1999)
ABSTRACT: A universally applicable model is presented for the calculation of the transport properties of ionized species in CFD simulations. A multicomponent mixture formulation and simple mixing rules are used to compute the transport coefficients of dissociated and ionized air from room temperature up to 30000 K at different pressures. Both formulations share little input data, which simplifies the handling of the transport model. The calculated binary diffusion coefficients are similar to the results of Levin et al.1-3 and Capitelli et al.4 The computed transport coefficients of the mixture are compared to the results of Gupta et al.5 A good agreement is found in the temperature range below 10000 K. At higher temperatures the results differ, because of the differences in the collision integrals of neutral-ion and Coulomb interactions and because of the use of higher approximations of transport properties of electrons in the present model.